2019
DOI: 10.21315/mjde2019.21.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Washback Effect of Final Examinations at Payame Noor University on Teaching and Learning

Abstract: The notion of washback is a prominent concept in language teaching and testing. Examinations are considered to be powerful determiners of what goes on in classrooms and their results can play a significant role in setting educational standards of an institution. Moreover, awareness of the possible negative or positive consequences of certain modes of assessment can enhance teachers' as well as learners' level of self-direction in the process of language acquisition. The connection between testing, teaching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Besides, this finding seems to support the opinion of Zheng [78] that Chinese national matriculation tests influence what and how students learn negatively. However, this result does not seem to support the view of Moradi [77] who claims that final examinations have a positive washback effect on learning. This finding suggests that students are forced to have abandoned learning practices that will broaden their understanding of concepts and issues in economics by going in using WASSCE Economics past question and solution books instead of standard economics textbooks.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Besides, this finding seems to support the opinion of Zheng [78] that Chinese national matriculation tests influence what and how students learn negatively. However, this result does not seem to support the view of Moradi [77] who claims that final examinations have a positive washback effect on learning. This finding suggests that students are forced to have abandoned learning practices that will broaden their understanding of concepts and issues in economics by going in using WASSCE Economics past question and solution books instead of standard economics textbooks.…”
Section: Discussioncontrasting
confidence: 97%
“…Moreover, the findings of the study indicated that the BECE/WASSCE English language test exerted a negative washback effect on students' learning practices. Again, Moradi [77] conducted a study on the washback effect of final examinations on teaching and learning. The results indicated that Payame Noor University (PNU), English and Foreign Languages (EFL) final examinations have a washback effect on learning and this washback effect is more positive than negative.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies (e.g., [8,[43][44][45][46][47][48][49][50][51][52][53][54][55]) have provided evidence for the washback effects of high-stakes test on teaching and learning. Whilst some studies discovered that high-stakes test has negative washback effects on classroom instructional practices (e.g., [51,[56][57][58]), others found that the effect was both positive and negative (e.g., [50,59]). Moreover, other studies were not able to reveal whether the washback was positive or negative (e.g., [46,60]).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Empirical findings have revealed that the washback effect of a high-stakes test can be both positive and negative [50,59]. From the model, a high-stakes test (WASSCE Economics examination) is likely to have washback effects on both Economics teachers and students.…”
Section: Proposed Model For Washback Effect Of High-stakes Testmentioning
confidence: 99%